Design out crime in school measuring validity and reliability sense of safety in secondary school : a pilot survey / Azna Abdul Wahab and Siti Rasidah Md Sakip - Azna, Abdul Wahab; Siti Rasidah, Md Sakip (Universiti Teknologi MARA, Perak, 2017)
The paper presents the reliability and validity of the 71 items in the questionnaire. A pilot survey was conducted at secondary school in Seri Iskandar Perak to measure the validity and reliability of the instrument. A random sample of53 students from Form 1 and Form 2 students.The results found the level reliability and validity using Cronbach Alpha (a) index for all components of sense of safety are 0.70 and above.